Colistimethate sodium powder and tobramycin powder for inhalation for the treatment of chronic Pseudomonas aeruginosa lung infection in cystic fibrosis: systematic review and economic model - P Tappenden; S Harnan; L Uttley; M Mildred; C Carroll; A Cantrell (Health Technology Assessment, 2013)
Background: Cystic fibrosis (CF) is an inherited condition characterised by the abnormal transport of chloride ions across transporting epithelia. This leads to the production of thick sticky mucus in the lungs, pancreas, liver, intestine and reproductive tract, and an increase in the salt content in sweat. Among other problems, people with CF experience recurrent respiratory infections and have difficulties digesting food. CF affects over 9000 individuals in the UK. CF shortens life expectancy and adversely affects quality of life. In 2010, CF was recorded as the cause of 103 deaths in England and Wales. Objective: To evaluate the clinical effectiveness and cost-effectiveness of colistimethate sodium dry powder for inhalation (DPI) (Colobreathe®, Forest Laboratories) and tobramycin DPI (TOBI Podhaler®, Novartis Pharmaceuticals) for the treatment of Pseudomonas aeruginosa lung infection in CF. Data sources: Electronic databases were searched in February and March 2011 [MEDLINE, MEDLINE In-Process & Other Non-Indexed citations, EMBASE, The Cochrane Library databases, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, Conference Proceedings Citation Index (CPCI) and Bioscience Information Service (BIOSIS) Previews]. Relevant databases were searched for ongoing and unpublished studies, and bibliographies of relevant systematic reviews and the manufacturers’ submissions were also hand-searched. Review methods: A systematic review of the clinical effectiveness and cost-effectiveness of colistimethate sodium DPI and tobramycin DPI for the treatment of chronic P. aeruginosa lung infection in CF was conducted. Existing economic evidence within the literature was reviewed and a de novo health economic model was also developed. Results: Three randomised controlled trials (RCTs) were included in the clinical effectiveness review. Both colistimethate sodium DPI and tobramycin DPI were reported to be non-inferior to nebulised tobramycin for the outcome forced expiratory volume in first second percentage predicted (FEV1%). It was not possible to draw any firm conclusions as to the relative efficacy of colistimethate sodium DPI compared with tobramycin DPI. The economic analysis suggests that colistimethate sodium DPI produces fewer quality-adjusted life-years (QALYs) than nebulised tobramycin. Given the incremental discounted lifetime cost of tobramycin DPI compared with nebulised tobramycin, it highly unlikely that tobramycin DPI has an incremental cost-effectiveness ratio that is better than £30,000 per QALY gained. Limitation: The uncertainty surrounding the short-term evidence base inevitably results in uncertainty surrounding the long-term clinical effectiveness and cost-effectiveness of colistimethate sodium DPI. Conclusions: Both DPI formulations have been shown to be non-inferior to nebulised tobramycin as measured by FEV1%. The results of these trials should be interpreted with caution owing to the means by which the results were analysed, the length of follow-up, and concerns about the ability of FEV1% to accurately represent changes in lung health. Although the increase in QALYs is expected to be lower with colistimethate sodium DPI than with nebulised tobramycin, a price for this intervention had not been agreed at the time of the assessment. Depending on the price of colistimethate sodium DPI, this results either in a situation whereby colistimethate sodium DPI is dominated by nebulised tobramycin or in one whereby the incremental cost-effectiveness of nebulised tobramycin compared with colistimethate sodium DPI is in the range of £24,000–277,000 per QALY gained. The economic analysis also suggests that, given its price, it is unlikely that tobramycin DPI has a cost-effectiveness ratio of < £30,000 per QALY gained when compared with nebulised tobramycin. A RCT to assess the longer-term (≥ 12 months) efficacy of colistimethate sodium DPI and tobramycin DPI in comparison with nebulised treatments would be beneficial. Such a study should include the direct assessment of HRQoL using a relevant preference-based instrument. Future studies should ensure that the European Medicines Agency guidelines are adhered to. In addition, high-quality research concerning the relationship between forced expiratory volume in first second % (FEV1%) predicted or other measures of lung function and survival/health-related quality of life (HRQoL) would be useful. Study registration: PROSPERO CRD42011001350. Funding: The National Institute for Health Research Health Technology Assessment programme.